Efficacy of colistin in multidrug-resistant neonatal sepsis: experience from a tertiary care center in Karachi, Pakistan. Issue 9 (20th March 2020) - Ambreen, Gul; Salat, Muhammad Sohail; Hussain, Kashif; Raza, Syed Shamim; Ali, Umer; Azam, Iqbal; Iqbal, Junaid; Fatmi, Zafar
Abstract : Objective: Infections with multidrug-resistant organisms (MDROs) such as Gram-negative bacteria have high morbidity and mortality with limited treatment options. Colistin, an antibiotic active against MDRO, was rarely used due to frequent adverse effects, but its use has now been recommended among adults. In this study, we determined the efficacy of colistin for the treatment of sepsis in neonates. Design/setting/patients/outcomes: We conducted a retrospective record review of all neonates admitted to the neonatal intensive care unit of Aga Khan University Hospital, Karachi, Pakistan, between June 2015 and June 2018, who had sepsis and received colistin by intravenous, inhalation and/or intrathecal routes. Predictors of colistin efficacy, for neonatal survival and microbial clearance, were assessed using multiple logistic regression. Results: 153 neonates received colistin; 120 had culture-proven sepsis; and 93 had MDR-GNB (84 colistin-sensitive). 111 (72.5%) neonates survived and were discharged from hospital; 82.6% had microbial clearance. Neonates with colistin-sensitive bacteria (adjusted OR (AOR)=3.2, 95% CI 2.8 to 4.0), and those in which colistin therapy started early (AOR=7.2, 95% CI 3.5 to 13.6) were more likely to survive. Neonates with increased gestational age (AOR=1.9, 95% CI 1.5 to 3.0), higher weight (AOR=5.4, 95% CI 3.3 to 11.8) and later onset of sepsis (AOR=4.3, 95% CI 2.0 to 9.0) had higher survival. Adverse events included nephrotoxicity in 5.2%; 13.7% developed seizures and 18.3% had electrolyte imbalance. Conclusions: Colistin therapy was associated with survival among neonates suffering from MDR-GNB sepsis. The frequency of side effects was moderate.